The effect of different types of food consumed on interstitial blood glucose levels – A case report - Mageshwari, Uma; Trueman, Patricia; Krishnan, Dharini; Viswanathan, Vijay (Indian Journal of Case Reports, 2020)
Dietary factors influence blood glucose levels. We report the case of a 57-year-old female with 8 years history of Type 2 diabetes mellitus. She does a physical activity like cycling 5 days a week for 45 min and does yoga 3 days a week for 30 min. She was on tablets gliclazide in the morning and sitagliptin combination with metformin in the night. The continuous glucose monitor tracked the blood glucose levels on different diets which were taken for 5 days. In this report, higher dietary fiber in little millet and finger millet maintained the blood glucose levels well within limits even at 90 min after the intake of the meal. Breakfast with mixed fruits and cereals increases postprandial sugar levels. It is very important how we mix different types of foods in a particular meal as it tends to affect postprandial blood glucose levels.